2015
DOI: 10.1021/acs.cgd.5b01236
|View full text |Cite
|
Sign up to set email alerts
|

Designing Chiral, Pro-Polar Structures for Observing Ferroelectricity: Molecular Analogue of KNO3

Abstract: Observation and creation of a pro-chiral center is a prerequisite in chemical synthesis for generating chiral structures. On the other hand, temporary and reversible generation of chiral or polar structures using physical forces such as electricity is a need of present technology for observing nonlinear behavior. Thus, one can synthesize a pro-polar structure, akin to a pro-chiral center using chemical interactions, for facilitating physical forces in generating chiral/polar structures, a novel way for designi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For example, the Leigh , and Aida groups demonstrated that inorganic nanocluster “wheels” are penetrable by finite or infinite organic “axles”, and more recently a tetrasilver cluster was shown to reside in a polypyridine macrocycle, forming a hybrid inorganic–organic pseudorotaxane; Dan Li’s Group reported a 1D hybrid polypseudorotaxane composed of mechanically interlocked infinite inorganic “axles” and finite organic “wheels” . This kind of hybrid polypseudorotaxane material not only combines the respective beneficial characteristics of inorganic and organic components, but also often exhibits unique properties that exceed what would be expected for a simple mixture of the components. However, the rational design and fabrication of 2D polypseudorotaxane remains a great challenge, and few examples have been reported. Cartoon representations of rotaxane and 1D and 2D polypseudorotaxane are shown in Figure .…”
mentioning
confidence: 99%
“…For example, the Leigh , and Aida groups demonstrated that inorganic nanocluster “wheels” are penetrable by finite or infinite organic “axles”, and more recently a tetrasilver cluster was shown to reside in a polypyridine macrocycle, forming a hybrid inorganic–organic pseudorotaxane; Dan Li’s Group reported a 1D hybrid polypseudorotaxane composed of mechanically interlocked infinite inorganic “axles” and finite organic “wheels” . This kind of hybrid polypseudorotaxane material not only combines the respective beneficial characteristics of inorganic and organic components, but also often exhibits unique properties that exceed what would be expected for a simple mixture of the components. However, the rational design and fabrication of 2D polypseudorotaxane remains a great challenge, and few examples have been reported. Cartoon representations of rotaxane and 1D and 2D polypseudorotaxane are shown in Figure .…”
mentioning
confidence: 99%